Perception of Green Spaces Preparedness and Accessibility During COVID-19: An Exploratory Survey in Two Mid-Sized Chilean Cities - Rojas Quezada, Carolina; Aguilera Sáez, Felipe; Vecchio, Giovanni; Steiniger, Stefan (Frontiers in Sustainable Cities, 2022)
Urban green spaces have shown to be beneficial for the physical and mental wellbeing of the general population—which particularly holds true during an unprecedented, stressful situation such as the COVID-19 pandemic. In urban settings characterized by structural inequality, scarce access to green spaces in a neighborhood can affect the wellbeing of its inhabitants and lower overall resilience of a community. Assuming that the effects of confinement and working from home produce an increased demand for recreational and sports activities, this paper looks to assess the level of preparedness and accessibility of green spaces during the COVID-19 pandemic, considering individual and public measures to avoid contagion. The assessment is carried out through an online exploratory survey and accessibility calculations that are applied to two Chilean cities with a Mediterranean climate, Talca and Chillán. The study considers the quality of green spaces based on (i) official statistics and (ii) a questionnaire directed toward residents. We found that high-quality urban green spaces are accessible to residents of both cities, but rather limited in December 2020 due to low levels of preparedness. Considering the qualities of existing urban green spaces allows for a more precise estimate of their contribution to the wellbeing of neighborhoods, and consequently facilitates better recommendations for urban plans and policies.